Avessos do excesso: a assexualidade - Bezerra, Paulo Victor [UNESP] (2015)
The Asexuals define themselves as people who do not experience sexual attraccion. The idea of an asexual individual brings up discussions about the political uses of sex, calls into question the epistemology of sexuality and raises debates about contemporary modes of subjectification. This thesis presents the scientific development of asexuality and outlines some understanding on the issue. The first chapter provides a detailed narrative of all the scientific writings on asexuality, covering every article and book published until now, including the early sources that somehow are related to it. These researches were compiled intending to rebuild identify and contextualize the first mentions to the idea of asexuality as well as the unfolding of the asexual's virual communities, which boosted the scientific production on this field. It is noted that the scientific production on asexuality is much like the scientific production on sexuality, rendering the main focusses of the last: the widely held task of legitimating, universalizing and naturalizing, commonly under a biological approach, but it also contains a fewer critical works, aligned with the policies of identity and uses of sex. The second chapter takes asexuality, instead of the asexual individuals, as object of study. Grounded on some articles, on the virtual sites of meeting as well as on some contemporary psychosocial theorists, a possibility of understanding about the group is presented, identifying it as a virtual tribe. Moreover, the ideas of simulacra society, spectacle society, the semblance subject and the subjectivity built over immaterial labor, amongst others, are coordinated in order to comprehend the emergency of asexuality and its position in the present, picturing it as both a form of subjectivation and of resistance. The third chapter reaches to position asexuality within the readings of Foucault's History of Sexuality...